Evaluating the Effectiveness of Teaching Factory in Culinary Education Using Tyler’s Goal-Oriented Model: A Case Study from an Indonesian Vocational School - Emi Vovo Sembiring; Sukardi Sukardi; Elida Elida; Muhammad Giatman (AL-ISHLAH: Jurnal Pendidikan, 2025)
The Teaching Factory (TEFA) is an educational model designed to bridge the gap between vocational training and industry demands by integrating real-world production experiences into the learning process. While TEFA aims to develop both technical and soft skills, its effectiveness remains underexplored, particularly in rural contexts. This study employed a descriptive qualitative approach using Tyler’s Goal-Oriented Evaluation Model to assess the implementation of TEFA in the Culinary Program at SMK Negeri 1 Lubuk Sikaping, Indonesia. Data were collected through in-depth interviews, participatory observations, and document analysis. Informants included school leaders, teachers, students, and industry partners. Data triangulation and thematic analysis were used to ensure validity. Findings revealed that while TEFA was fully integrated into daily instructional activities and contributed to students’ technical competence and work readiness, the program fell short in several key areas. These include: (1) vague and non-measurable objectives, (2) lack of alignment between activities and goals, (3) absence of standardized soft skills assessment tools, (4) informal and inconsistent evaluation practices, (5) limited data documentation, and (6) insufficient industry collaboration in performance evaluation. Despite its strengths in fostering industry-like experiences, TEFA’s effectiveness is constrained by gaps in planning, assessment, and feedback systems. Strengthening evaluation protocols, developing rubrics for soft skills, and integrating digital tools for performance tracking are essential to align TEFA with its intended outcomes.